2023
DOI: 10.3389/fendo.2023.1120779
|View full text |Cite
|
Sign up to set email alerts
|

Blood glucose level affects prognosis of patients who received intravenous thrombolysis after acute ischemic stroke? A meta-analysis

Abstract: Background and objectivesIntravenous recombinant tissue plasminogen activator (rtPA) thrombolysis is an effective treatment for acute ischemic stroke. Hyperglycemia is a major risk factor for the occurrence, development, and prognosis of ischemic stroke. This meta-analysis purposefully estimates the association between hyperglycemia and poor prognosis in acute ischemic stroke patients receiving intravenous rtPA thrombolytic therapy.Materials and methodsAccording to the predefined inclusion criteria, we searche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
2
1
0
Order By: Relevance
“…The third factor that enhances the model's predictive accuracy is the RBS level obtained at the presentation. This study corroborates previous research by demonstrating a correlation between higher RBS levels at admission and an unfavorable prognosis [46]. In this study, the mean RBS was 9.3 ± 4.6 mmol/L, and the average RBS of patients with an unfavorable mRS at 90 days was significantly higher than that of the favorable group (9.9 vs. 8.7, with a p-value below 0.05).…”
Section: Discussionsupporting
confidence: 91%
“…The third factor that enhances the model's predictive accuracy is the RBS level obtained at the presentation. This study corroborates previous research by demonstrating a correlation between higher RBS levels at admission and an unfavorable prognosis [46]. In this study, the mean RBS was 9.3 ± 4.6 mmol/L, and the average RBS of patients with an unfavorable mRS at 90 days was significantly higher than that of the favorable group (9.9 vs. 8.7, with a p-value below 0.05).…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, patients with initially elevated blood glucose levels had poorer usual activity scores. This finding correlates with the results of a recent meta-analysis, showing that acute stroke patients with elevated blood glucose levels who received systemic thrombolytic therapy had a worse outcome as measured by mRS at 90 days and a higher rate of symptomatic intracerebral haemorrhage [ 49 ]. Possible mechanisms for such detrimental effects of hyperglycaemia have been discussed and include exacerbation of pathophysiological mechanisms such as thrombo-inflammation known to negatively impact infarct evolution final outcome [ 9 , 11 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 88%
“…16 Epidemiological studies have demonstrated that an extended period of elevated hyperglycemia is associated with magnified infarct dimensions, heightened susceptibility to reperfusion complications, deterioration of stroke-related lesions, and potentially elevated mortality rates. 17 Currently, the precise mechanism underlying the aggravation of brain damage due to glucose fluctuations remains incompletely elucidated. However, several potential rationales exist for this phenomenon.…”
Section: Discussionmentioning
confidence: 99%